Physicochemical and Electrochemical Properties of 1, 1, 2, 2‐Tetrafluoroethyl‐2, 2, 3, 3‐Tetrafluoropropyl Ether as a Co‐Solvent for High‐Voltage Lithium‐Ion Electrolytes. Issue 14 (23rd July 2019) - Xia, Lan; Lee, Saixi; Jiang, Yabei; Li, Shiqi; Liu, Zhaoping; Yu, Linpo; Hu, Di; Wang, Shuhan; Liu, Yitong; Chen, George Z.
Abstract: Although high‐voltage positive electrode materials for high energy density lithium‐ion batteries have gained a great attention, the lack of compatible electrolytes with sufficiently high oxidative stability to deliver an excellent cycling ability restricts their practical application. Fluorinated solvents are considered as promising candidates for high‐voltage electrolyte solvents. In this study, we select 1, 1, 2, 2‐tetrafluoroethyl‐2, 2, 3, 3‐tetrafluoropropyl ether (TTE) with a high boiling point, low cost, and good SEI‐filming ability as a co‐solvent of fluoroethylene carbonate‐based electrolytes and extensively investigate its physicochemical and electrochemical properties for applications in high‐voltage lithium‐ion batteries. Our experimental results show that the TTE‐containing electrolyte exhibits not only a high oxidative stability up to 5.5 V ( vs . Li/Li + ), but also excellent wettability with the separator. In addition to high discharge capacity and increased coulombic efficiency of the Li/LiNi0.5 Mn1.5 O4 half‐cell assembled with the TTE‐containing electrolyte cycled between 3.0 and 4.9 V, the cell also displays a high rate capability. This work shows that partially fluorinated ethers, e. g., TTE, are promising co‐solvents for high‐voltage electrolytes that can enable commercial development of high energy density lithium‐ion batteries. Abstract : Co‐solving the problem : 1, 1, 2, 2‐Tetrafluoroethyl‐2, 2, 3, 3‐tetrafluoropropyl ether (TTE) is of high boiling point, low cost, and good SEI‐filming ability and is used here as a co‐solvent for fluoroethylene carbonate‐based electrolytes. It is demonstrated to be suitable for high‐voltage application enabling commercially desirable high energy density lithium‐ion batteries.